Ovarian fibroma with luteinized thecal cells and minor sex cord element: A rare case report - Anjali Mathur; Ankit Seth; Leela Pant (Wolters Kluwer Medknow Publications, 2018)
Ovarian fibroma with minor sex cord element (MSCE) is a rare tumor. The increased estrogen production due to the presence of MSCE and/or luteinized thecal cells within fibroma can be a risk factor for endometrial hyperplasia or carcinoma.